assignment 19

#$&*

course mth 173

time 1945date 18 aug 2010

019. `query 19

*********************************************

Question: `qQuery problem 3.4.27 was 3.4.29 (3d edition 3.4.20) was 4.4.12 Derivative of `sqrt( (x^2*5^x)^3

What is the derivative of the given function?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

5^3x/2(3*ln5*[x^3]/2+3x*[x]

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** The function is `sqrt( (x^2 * 5^x)^3 ) = (x^2 * 5^x)^(3/2).

This is of form f(g(x)) with g(x) = x^2 * 5^x and f(z) = z^(3/2). Thus when you substitute you get f(g(x)) = g(x)^(3/2) = (x^2 * 5^x)^(3/2).

(x^2 * 5^x) ' = (x^2)' * 5^x + x^2 * (5^x) ' =

2x * 5^x + x^2 ln 5 * 5^x =

(2x + x^2 ln 5) * 5^x.

`sqrt(z^3) = z^(3/2), so using w(x) = f(g(x)) with f(z) = z^(3/2) and g(x) = x^2 * 5^x we get

w ' = (2x + x^2 ln 5) * 5^x * [3/2 (x^2 * 5^x)^(1/2)] = 3/2 (2x + x^2 ln 5) * | x | * 5^(1/2 x).

Note that sqrt(x^2) is | x |, not just x, since the square root must be positive and x might not be. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*

*********************************************

Question: `qQuery problem 3.4.26 was 3.4.28 (3d edition 3.4.19) (was 4.4.20) derivative of 2^(5t-1).

What is the derivative of the given function?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(5*ln(2)*32^t)/2

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThis function is a composite. The inner function is g(x)=5t-1 and the outer function is f(z)=2^z.

f'(z)=ln(2) * 2^z.

g ' (x)=5

so

(f(g(t)) ' = g ' (t)f ' (g(t))=

5 ln(2) * 2^(5t-1).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*

*********************************************

Question: `q**** Query 3.4.67 was 3.4.68 (3d edition 3.4.56) y = k (x), y ' (1) = 2.What is the derivative of k(2x) when x = 1/2?

What is the derivative of k(x+1) when x = 0?

{]What is the derivative of k(x/4) when x = 4?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: the der of k(2x) when x=1/2 is 4 and the der of k(x+1) when x=0 is 2. And the der when k(x/4) is ½.

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** We apply the Chain Rule:

( k(2x) ) ' = (2x) ' * k'(2x) = 2 k(2x).

When x = 1/2 we have 2x = 1.

k ' (1) = y ' (1) = 2 so

when x = 1/2

( k(2x) ) ' = 2 k(2 * 1/2) = 2 * k'(1) = 2 * 2 = 4.

(k(x+1)) ' = (x+1)' k ' (x+1) = k ' (x+1) so

when x = 0 we have

(k(x+1) ) ' = k ' (x+1) = k ' (1) = 2

(k(x/4)) ' = (x/4)' k'(x/4) = 1/4 * k'(x/4) so when x = 4 we have

(k(x/4))' = 1/4 * k'(x/4) = 1/4 k'(4/4) = 1/4 * 2 = 1/2. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*

*********************************************

Question: `qQuery 3.4.81 (3d edition 3.4.68). Q = Q0 e^(-t/(RC)). I = dQ/dt.

Show that Q(t) and I(t) both have the same time constant.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

To read the solution!

confidence rating #$&*

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** We use the Chain Rule.

(e^(-t/(RC)))' = (-t/(RC))' * e^(-t/(RC)) = -1/(RC) * e^(-t/(RC)).

So dQ/dt = -Q0/(RC) * e^(-t/(RC)).

Both functions are equal to a constant factor multiplied by e^(-t/(RC)).

The time constant for both functions is therefore identical, and equal to RC. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok This helps I needed to read the solution to grasp the concept but I think I understand better now. This chain rule thing is very grey to me right now but coming back.

------------------------------------------------

Self-critique rating #$&* 1.95

*********************************************

Question: `qQuery problem 3.5.5 (unchanged since 3d edition) (formerly 4.5.6). What is the derivative of sin(3x)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

It is 3*sin(3x)

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** sin(3x) is the composite of g(x) = 3x, which is the 'inner' function (the first function that operates on the variable x) and the 'outer' function f(z) = sin(z).

Thus f(g(x)) = sin(g(x)) = sin(3x).

The derivative is (f (g(x) ) ' = g ' (x) * f' ( g(x) ).

g ' (x) = (3x) ' = 3 * x ' = 3 ', and

f ' (z) = (sin(z) ) ' = cos(z).

So the derivative is [ sin(3x) ] ' = ( f(g(x) ) ' = g ' (x) * f ' (g(x) ) = 3 * cos(3x). **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

ok

------------------------------------------------

Self-critique rating #$&*2

*********************************************

Question: `qQuery problem 3.5.50 was 3.5.48 (3d edition 3.5.50) (formerly 4.5.36). Give the equations of the tangent lines to graph of y = sin(x) at x = 0 and at `pi/3

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

X=0, y=1 and has a slope of 1 through point 0,0

X=sin(pi/3) and y= cos pi/3.

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** At x = 0 we have y = 0 and y ' = cos(0) = 1.

The tangent line is therefore the line with slope 1 through (0,0), so the line is y - 0 = 1 ( x - 0) or just y = x.

At x = `pi/3 we have y = sin(`pi/3) = `sqrt(3) / 2 and y ' = cos(`pi/3) = .5.

Thus the tangent line has slope .5 and passes thru (`pi/3,`sqrt(3)/2), so its equation is

y - `sqrt(3)/2 = .5 (x - `pi/3)

y = .5 x - `pi/6 + `sqrt(3)/2. Approximating:

y - .87 = .5 x - .52. So

y = .5 x + .25, approx.

Our approximation to sin(`pi/6), based on the first tangent line:

The first tangent line is y = x. So the approximation at x = `pi / 6 is

y = `pi / 6 = 3.14 / 6 = .52, approximately.

Our approximation to sin(`pi/6), based on the second tangent line, is:

y = .5 * .52 + .34 = .60.

`pi/6 is equidistant from x=0 and x=`pi/3, so we might expect the accuracy to be the same whichever point we use.

The actual value of sin(`pi/6) is .5. The approximation based on the tangent line at x = 0 is .52, which is much closer to .5 than the .60 based on the tangent line at x = `pi/3.

The reason for this isn't too difficult to see. The slope is changing more quickly around x = `pi/3 than around x = 0. Thus the tangent line will move more rapidly away from the actual function near x = `pi/3 than near x = 0. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I don’t understand why that the values for my results are so different from the results you obtained for instance the sin (pi/3) decimal values are way off from yours what is your guess.calculator?

I don't see your values, but if they differ greatly from the values in the problem, chances are it's because you're using the calculator (probably in degree mode, which is never used in calculus).

You should know the trigonometric functions of the angles which are multiples of pi/4 and pi/6. The sine of pi/6 is sqrt(3) / 2, which is about .87.

------------------------------------------------

Self-critique rating #$&*2

*********************************************

Question: `qQuery 3.5.34 (3d edition 3.5.40). Der of sin(sin x + cos x)

What is the derivative of the given function and how did you find it?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

It is the cosx-sinx * cosx(sinx+cosx)

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThe function y = sin( sin(x) + cos(x) ) is the composite of g(x) = sin(x) + cos(x) and f(z) = sin(z).

The derivative of the composite is g ' (x) * f ' (g(x) ).

g ' (x) = (sin(x) + cos(x) ) ' = cos(x) - sin(x).

f ' (z) = sin(z) ' = cos(z).

So g ' (x) * f ' (g(x)) = ( cos(x) - sin(x) ) * cos( sin(x) + cos(x) ).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

Ok I missed the x on the second part and added it inn.

------------------------------------------------

Self-critique rating #$&*

*********************************************

Question: `qQuery Add comments on any surprises or insights you experienced as a result of this assignment.

The old way of doing this ie without electronic devices is critical to passing Dave Smiths Courses.

That's not the 'old way', it's the only way. The calculator adds nothing to the understanding we need in order to understand the behavior of various systems. The calculator is a convenience but if misused it allows us the illusion of understanding without the substance.

#$&*